2014
DOI: 10.18632/oncotarget.1736
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor-1 alpha as a therapeutic target in multiple myeloma

Abstract: The increasing importance of hypoxia-inducible factor-1α (HIF-1α) in tumorigenesis raises the possibility that agents which specifically inhibit this transcription factor, would provide significant therapeutic benefit. The constitutive expression of HIF-1α in about 35% of Multiple Myeloma (MM) patients suggests HIF-1α suppression might be part of a therapeutic strategy. Accordingly, we explored the effect of EZN-2968, a small 3rd generation antisense oligonucleotide against HIF-1α, in a panel of MM cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…The inner mitochondrial membrane potential was measured by staining cells with 20 nM tetramethylrhodamine methyl ester (TMRM) (Molecular Probes, Eugene, OR), a lipophilic probe that enters mitochondria in a ⌬ m -dependent manner (25). The cells were incubated with the probe for 30 min at 37°C in the absence or presence of 0.6 M oligomycin and wells were then washed twice with Hanks' balanced salt solution to remove any remaining unincorporated dye.…”
Section: Sds-page and Westernmentioning
confidence: 99%
“…The inner mitochondrial membrane potential was measured by staining cells with 20 nM tetramethylrhodamine methyl ester (TMRM) (Molecular Probes, Eugene, OR), a lipophilic probe that enters mitochondria in a ⌬ m -dependent manner (25). The cells were incubated with the probe for 30 min at 37°C in the absence or presence of 0.6 M oligomycin and wells were then washed twice with Hanks' balanced salt solution to remove any remaining unincorporated dye.…”
Section: Sds-page and Westernmentioning
confidence: 99%
“…61,62 Recently, our group have tested the efficacy of EZN-2968 oligonucleotide in a panel of human MM cell lines and primary samples. 12,13 In these studies we showed that HIF-1α mRNA and protein are constitutively present in MM cells and are further inducible by BM milieu stimuli (such as IL-6 and IGF-1) even in normoxic culture conditions. In MM cells, HIF-1α suppression induced a permanent cell cycle arrest by prolonging S-phase through cyclin A modulation and in addition it induced a mild apoptotic cell death.…”
Section: Accepted Manuscriptmentioning
confidence: 88%
“…7 In the past few years, a growing number of studies have provided valuable insight into the important role of HIF-1α in the pathophysiology of MM. [8][9][10][11][12][13] Treatments targeting both HIF-1α and hypoxic microenvironments represent novel strategies to improve treatment outcomes for MM.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations